2D Materials for Wearable Energy Harvesting. Issue 9 (9th March 2022) - Lee, Meng Hao; Wu, Wenzhuo
Abstract: The growing demand for energy in wearable sensors and portable electronics necessitates the development of self‐contained, sustainable, and mobile power sources capable of harvesting environmental energies. Researchers have made significant strides in implementing photovoltaics, thermoelectrics, piezoelectrics, and triboelectrics in 2D materials. This has resulted in significant advancements in wearable energy harvesting systems based on 2D materials. This review discusses the relationship between synthesis procedures, material structures/properties, and device performance in the context of 2D materials‐based wearable energy harvesting technologies. Finally, challenges and future research opportunities are identified and discussed based on current progress. Abstract : Overview of 2D materials with unique structure, properties and prepared by various techniques in energy harvesting and application for human‐related applications.